Working Memory and Response Inhibition in Patients With Bipolar I Disorder During Euthymic Period - Farahmand, Zahra (Iran J Psychiatry Behav Sci, 2015)
BACKGROUND: Several cognitive domains, including attention, memory, and executive functions are impaired in bipolar disorder. OBJECTIVES: This study aimed to investigate two executive functions (working memory and response inhibition) in patients with bipolar I disorder during remission of the symptoms. PATIENTS AND METHODS: In this case-control design, 30 bipolar I patients (18 to 45 years old) were matched with 30 ones in the control group in terms of age, gender, and education. The patients were selected from Roozbeh Psychiatric Hospital (a hospital affiliated to Tehran University of Medical Sciences) from May to October 2013. They were evaluated and contrasted using working memory (Spatial Span and Spatial Working Memory (SSP and SWM)) and response inhibition (Stop Signal Task (SST)) tests. RESULTS: We used independent t-tests for comparing and contrasting 2 groups on total and sub-scales scores of these 3 tests. In terms of SWM test there was a significant difference in between-group error between the two groups (P = 0.05); there was also a meaningful difference between the strategies used by two groups (P = 0.05). In SSP test, a significant difference appeared between averages of span length of the two groups. In the first and last item delays, there was also a clear difference, but the total error index was not noticeably different. In SST test, the direction error indicator in start-stop trials indicated a major difference, while in successful stops ratio, the case group had a lower ratio. In addition, reaction time to stop signs in bipolar group was meaningfully lower than the control group. CONCLUSION: In conclusion, even during remission phase, executive dysfunction is detectable at least in some areas in patients with bipolar disorder.